L’univers d’Astrid Lindgren à portée de main - Christophe Premat (Strenae)
This paper attempts to understand how children's cultural material is integrated into innovative pedagogical approaches in Sweden. In particular, we will look at how Astrid Lindgren's fictional universe materializes in children's museums (Junibacken in Stockholm, Ville Villekula in Småland). Children's museums have multiplied in Sweden, with invitations to attend readings, plays and productions about Swedish heroes (Bamse, Pettson and Findus bears). Schools themselves are invited to use these places as pedagogical levers to promote children's awareness. This article intends to show how these places promote the integration of children into a national narrative that puts a liberal pedagogy into perspective. We will discuss the museum dedicated to Astrid Lindgren's characters. Junibacken is all the more interesting because Astrid Lindgren participated in its creation. Children are guided by a story train that juxtaposes Astrid Lindgren's various characters (Emil, Karlsson-on-the-Roof, Pippi ...). Then the house of Pippi Longstocking (Fifi Brindacier) is represented upstairs, where children can manipulate and play with the universe of this character who became a national myth. These materializations reflect a specific mass culture for children, where the child's imagination is enchanted. At the same time, Swedish policies intend to protect children from all forms of harassment (such as the mobbing phenomenon) and physical punishment (such as the prohibition of spanking and all other physical force, banned within education).